Prevalence of Overweight and Obesity in Elementary School Students of vitoria, ES - Dalmaso, Suelen Borges; Sant'ana, Paula Grippa [UNESP]; Cordeiro, Joctan Pimentol; Rodrigues, Alexandre Loureiros; Ferreira, Lucas Guimaraes; Leopoldo, Andre Soares; Lima Leopoldo, Ana Paula (Centro Univ Sao Camilo, 2019)
Although numerous studies have analyzed overweight and obesity among schoolchildren from various Brazilian regions, the data relative to the state of Espirito Santo (ES) remains scarce. Considering the information presented, the purpose of present study was to investigate the prevalence of overweight and obesity among elementary school students from Vitoria, ES. This was a cross-sectional study including 572 school children between 7 to 14 years old enrolled in municipal elementary schools in Vitoria, ES, totalling 310 girls and 262 boys, who were randomly selected by stratified cluster sampling. The prevalence of overweight and obesity was calculated based on the children's anthropometric profile according to percentage of body fat by measuring skinfold thickness and body mass index (BMI). Based on BMI, the prevalence of overweight was high in both sexes, with 20.6% among the boys and 20.9% among the girls. The prevalence of obesity did not differ between boys and girls, with 6.5% and 7.7%, respectively. The results of the skin-fold thickness of skin show that 31.3% of children attending municipal schools in Vitoria/ES were classified as overweight. In summary, the current study found a high prevalence of overweight and obesity, reaffirming that the overweight reaches a significant proportion of children and adolescents who attend public elementary schools in the city of Vitoria, ES.
Keywords: Overweight; Obesity; Anthropometric Profile; Schoolchildren; Students